2023
DOI: 10.3390/ijerph20021540
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Therapeutic Healthcare Environmental Criteria: Architectural Designers’ Perspectives

Abstract: This study presents architectural designers’ perception of the importance of healthcare environmental criteria in the implementation of user-centered, therapeutic hospital design. Architectural designers with over three years of professional experience (N = 182) in South Korea were surveyed using an empirical questionnaire. The extensive interviews of 15 hospital design experts followed to interpret the survey results and discuss the barriers and suggestions for the successful delivery of therapeutic healthcar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 144 publications
0
3
0
Order By: Relevance
“…However, concerns about potential harm following ECMO application call for improved pre-ECMO counseling and support. These findings emphasize the pivotal role of communication and patient-centered care in refining ECMO clinical practices, ensuring they align with patients' preferences and needs [24][25][26] .…”
Section: Discussionmentioning
confidence: 75%
“…However, concerns about potential harm following ECMO application call for improved pre-ECMO counseling and support. These findings emphasize the pivotal role of communication and patient-centered care in refining ECMO clinical practices, ensuring they align with patients' preferences and needs [24][25][26] .…”
Section: Discussionmentioning
confidence: 75%
“…The presentation of the two case studies underlines how different spatial, physical design, and social and functional attributes are associated to different levels of spatial-physical humanization and their relationship with wellbeing. In this regard, recently, Cho [45] investigated architectural designers' point of view of the importance of healthcare environmental criteria in the implementation of user-centered, therapeutic hospital design, discussing the barriers and suggestions for the healthcare design practice. The environmental comfort quality criterion (i.e., illumination, climate comfort) has received attention in some publications, as environmental attributes affect hospital users' healing and well-being [46].…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Zhang conducted an in-depth study about the link between healthcare buildings and health based on the OHE framework, in which the researcher found that a complete framework requires an integrated consideration of the interplay of various environmental, resident, and health factors on patient recovery and healing [22]. Building on the OHE framework, the researcher proposed the Environment-Occupant-Health (EOH) framework, which provides an integrated perspective on how the essential features of hospital buildings impact the health and healing outcomes of residents, and these environmental features are interrelated [23]. The EOH framework includes three design principles, namely a comfortable environment, well-functioning and healing spaces, and a relaxing atmosphere (Table 1).…”
Section: Healing Framework Of Spacementioning
confidence: 99%